The Perspective of Physiotherapist on Playing Related Musculoskeletal Disorder among Amateur Piano Players - A., Ashish Mathew; Farzana, S. F. Mariyam; Suresh, T. N.; Veeragoudhaman, T. S. (Perspective of Recent Advances in Medical Research Vol. 5, 2023)
Music is an essential ingredient of any entertainment; Music plays a key role in connecting audience’s expectation with reality. Musician is the one, who brings life to music through art of his playing. In the year 18th century the first generation of piano known as forte piano was invented by Bartolomeo Cristofori. In 20th century the upright and grand piano were coined and distributed in market. To most of the public music is often perceived as fun and safe job without posing any harm to the body. There is a possibility for musicians to suffer from injuries. Pianist is prone injuries due to nature of musical practice. The present research has shown that Prevalence of PRMD among pianist has been reported in the range of 25%to 93%. The piano an acoustical musical instrument from a French origin is attracted and learned by many children’s across the globe. Posture plays a vital role in piano, correct balance and posture may achieve tension free playing. A piano player entertains the audience in a form of lullaby music; the journey of a player from amateur to professional is not easy as much we think, each phase of learning subsists many trails, exams, rehearsals. The main objective of this book is to prevent playing related musculoskeletal disorder among amateur musician which can significantly hinder their career and quit passion. This book concludes that many researches has to be conducted in different geographical part of India with distinct instruments in bringing out consequence of the term PRMD from mystery to history and let children’s dream may not be shattered down by it.